PENGARUH POLA ASUH ORANG TUA DAN TIPE KEPRIBADIAN SISWA TERHADAP KEMAMPUAN METAKOGNISI SISWA SLBN 3 LOMBOK TIMUR - Zinnurain, Zinnurain (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
This study aims to determine the effect of parenting style and student personality on the metacognition abilities of SLB Negeri 3 East Lombok students in the 2022/2023 academic year. The method used is ex post facto. The population in this study were all students of SLB Negeri 3 East Lombok in the even semester of the 2022/2023 school year. Samples were taken by multistage random sampling technique. The research design used was a 2 x 2 factorial group design. Data were collected and calculated using two-way analysis of variance (ANOVA). The results of the study concluded that: 1) the metacognitive abilities of students who were raised by permissive parenting were higher than students who were raised by authoritarian parenting, and 2) the metacognitive abilities of students who were raised with an extravert personality type were higher than those who were raised by an intravert personality type. Practically, educational institutions and families are advised to collaborate in developing students' metacognitive abilities so that the students of SLB Negeri 3 East Lombok and the people around them can feel the benefits.